Legal Cross-Dressing: Sexuality and the Americans with Disabilities Act - Malti-Douglas, Fedwa (Columbia Journal of Gender and Law, 2006)
The United States government wants its citizens to know that the Americans with Disabilities Act of 1990 (“ADA”) is about more than eliminating physical barriers and creating opportunities for employment. It is part of a larger project of breaking down stereotypes, dispelling myths, and quieting fears. Ironically, the ADA, in its application and jurisprudence, has probably done more to perpetuate stereotypes, myths, and fears than it has to eliminate them. The fears and stereotypes fostered by the ADA are not primarily about disabilities and their effects. Instead, these fears revolve around sexuality. How do handicaps connect to sexualities? They are linked through an anxiety of shifting marginalities. In addition to their attempts to order behavior or to balance interests and rights, legal texts and statutes reflect our obsessions and fascinations. Even when a legal text is associated with an individual, a specific court, or a legislative or regulatory body, it is the product of collective processes and reflects collective values. A piece of complex legislation like the ADA is a mine of hidden subtexts. These are most visible when the legal areas touch the areas of gender and sexuality. Michel Foucault and others have amply shown us that mental structures or mentalités can lead us down unexpected paths. Literary and cultural critics have made us aware that this is the case with artistic and cultural production. The law is no exception, as both legal specialists and literary critics have amply demonstrated: Robert Ferguson, Richard Posner, Stanley Fish, or Peter Brooks, to name but four. The imaginary is as critical in the law as it is elsewhere in our intellectual universe. It seems impossible to make sense of the Americans with Disabilities Act without examining the mentalities it embodies and the place of both the statute and its jurisprudence in the contemporary American imaginary.